Trend Gross Death Rate Dan Net Death Rate Per Tahun Di Rumah Sakit Pku Muhammadiyah Surakarta Tahun 2011-2015 - Pratama, Bangkit Ary; Parmadi, Anom (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2017)
Introduction Survey Based on RS PKU Muhammadiyah Surakarta Year 2011-2015 Already calculation GDR and NDR but yet does Against Value Creation trend GDR and NDR. And Mortality in PKU Muhammadiyah Surakarta Year 2011-2015 fluctuated.To identify trends GDR and NDR per year at PKU Muhammadiyah Hospital in Surakarta in 2011 - 2015. Research is descriptive, retrospective study design with overall sample population is a list of books hospitalizations Year 2011 - 2015 WITH univariate analysis, the data collected by observation and interviews. From the results of observation and calculation tin Value GDR Already below the national standard values Is 45% but still rose And Decline Of The Year 2011-2015 That is 20.22%, 20.11%, 16.97%, 18.66%, 15.19% And to review Also NDR Value Already below the national standard of 25% And Still Namely rose And Impairment NDR That is 11.09%, 6.86%, 7.13%, 9.39%, 7,92%. Trend GDR and NDR in Hospital Year 2011 - 2015 experienced a decline. GDR in 2011 Figures trend decreased 4.6 20.53 15.93 Become forecast for a review of 2016 figures NDR Value Score 14.73 while the trend was decreasing 1,52 9,25 7,73 Being And forecasts (Forecasting) 2016 figures 7, 35.